La nouvelle loi française sur la fin de vie. Premiers regards sur la loi du 2 février 2016 créant de nouveaux droits en faveur des malades et des personnes en fin de vie (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The paper focuses on the recent end-of-life law passed by the French Parliament in January 2016, highlighting the main changes with particular reference to the patient right to self-determination. The new law, which is undoubtedly based on the principle of patient autonomy, while formally strengthening the role of the patient wishes in cases of treatment withdrawal, proves to be more substantially innovative in increasing patient self-determination in decisions aimed at alleviating suffering. In this context, the article discusses one of the most sensitive issues in the French debate over end of life decisions, and namely the rule allowing doctors to carry out, under specific circumstances, a deep and continued sedation, altering consciousness until death. The paper also addresses the changes aimed at strengthening the role and binding value of advance decisions, as well as some gaps still affecting rules concerning protected adults.
Keywords: End-of-life; End-of-life; Deep and continuous sedation; Deep and continuous sedation; Double effect; Double effect; Patient rights; Patient rights; Advance decisions; Advance decisions